Ragam Konjungsi pada Rubrik Nusantara Surat Kabar Digital Mediaindonesia.com Edisi Mei 2021 dan Pemanfaatannya sebagai Bahan Ajar Teks Berita di Kelas VIII SMP - Rian Yoana; Oding Supriadi; Sahlan Mujtaba (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The purpose of this research was to find out various type of conjunction in the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition and to describe the use of various type of conjunction in the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition as teaching material for news texts in class VIII SMP. This research is a type of qualitative research which uses a qualitative descriptive method. The subjects in this study is the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition. The objects in the study is various type of conjunction which is in the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition. The data collection techniques of this research are observation and documentation. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. Based on research results in the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition it was found 88 various type of conjunction which consists of 39 coordinating conjunction and 49 subordinating conjunction. Research result various type of conjunction in the archipelago rubric digital newspaper Mediaindonesia.com May 2021 edition the next is used as teaching material for news texts in class VIII SMP.